SMART, DIGITAL SUPPLY CHAIN OF TOMORROW IS HERE TODAY how to enable a lean and agile global... supply chain with the help of technology. - MYERSON, PAUL (PRODUCTIVITY PRESS, 2025)
Technology plays a key role in enabling lean and agile supply chain operations. For example, connecting to suppliers in real-time facilitates re-supplying parts and materials for a just-in-time production environment. But choosing the wrong technology can create waste in terms of the time, effort, and money spent evaluating, selecting, implementing, and using it.Furthermore, lean has been traditionally thought of as a "pen and pencil" technique as they were mostly confined to a single facility. As a consequence, while there are many books written on lean manufacturing, lean office, and, to a lesser degree, lean global supply chain, most if not all barely discuss the role and impact of technology in process improvement, and there aren't many books that combine the topics of a lean and agile supply chain and technology (smart and otherwise) in this way.This book makes the case that technology is a key enabler of a lean supply chain and is unique in that it links lean and agile thinking with available and affordable technologies to get the most out of improved processes.Essentially, this book details various supply chain and logistics management areas where lean and agile thinking in combination with existing and emerging technologies such as the Internet, e-commerce, Enterprise Resource Planning (ERP) systems, Robotics, IoT, AI, and Data Analytics can take an organization to the next level through increased speed, accuracy, integration, and collaboration among all parties in the supply chain.